QAḌIYAT AL-ISLĀMAWIYYAH, SIYĀSAT AL-HAWIYYA, WA AL-SHABĀB AL-INDŪNISIY FĪ ‘AṢR MĀ BA’D AL-ḤAQĪQAH (JOURNAL OF INDONESIAN ISLAM, 2024)
This article highlights the influence of Islamism and identity politics on Indonesian younger generation in the post truth era by emphasizing on the role of information technology and social media in spreading those ideologies. The research uses mixed methods of combining quantitative analysis with qualitative analysis, in which data are collected though questionnaire and interviews with those Indonesian Muslim youths as well as employing content analysis of social media accounts, religious publication, and education background. The results indicate that social media plays major role among the youths in the spread of Islamism ideas, whereas social, economic, and political factors significantly influence the acceptance of those ideologies. In addition, the institutions of education and religion shape the awareness of the youths, but curriculum improvement is still needed to promote religious pluralism and national resilience. This article recommends the reinforcement of national identity and cultural pluralism, including education policy  which will withstand the intrusion of Islamism  and identity politics in Indonesia.